Service Restoration in Distribution Networks by Optimal Scheduling of Repair Crew and Mobile Power Sources - Qasem Asadi; Hamid Falaghi; Ali Ashoornezhad; Maryam Ramezani (AUT Journal of Electrical Engineering, 2024)
Power distribution utilities need to have an effective and suitable service restoration (SR) plan to reconnect customers quickly after power outages. This article presents a heuristic bi-stage SR algorithm that first re-energizes some of the loads fast by remote-controlled switches (RCSs) in the first stage and then continues to restore the rest of the network in the second stage with all possible switching actions using RCSs and manual switches (MSs). This study also includes finding the optimal Switching Sequences (SSs) and the estimated energy not supplied  (EENS) as an objective function. Moreover, the proposed method is more attractive and practical because it considers the time of occurrence of the failure and the daily load curve, the location of the load transfer capability, and the traffic conditions of the network. In this method, repair crew (RC) and mobile power sources (MPSs) are also important for the restoration process. The heuristic SR algorithm was tested on a standard IEEE 70-bus system in different scenarios. The results showed a significant difference in the solutions to the problem and the ENS in different scenarios. Lastly, it was concluded that this heuristic method would produce optimal, precise, and feasible solutions for SR in distribution networks.